Efficiency of UVA LEDs grown by HVPE in relation with the active region thickness. Issue 4 (18th March 2015) - Kurin, Sergey; Antipov, Andrey; Barash, Iosif; Roenkov, Alexander; Usikov, Alexander; Helava, Heikki; Makarov, Yuri; Solomonov, Alexander; Tarasov, Sergey; Evseenkov, Anton; Lamkin, Ivan
Abstract: We report on results of the performance study of UVA LEDs depending on the thickness of the active region. UVA LEDs are based on GaN/AlGaN heterostructures grown on Al2 O3 (0001) substrates by hydride vapor phase epitaxy (HVPE). It is shown that the use of thick (̴ 100 nm) single layer as the active region of UVA LED is a promising concept to achieve enhanced efficiency. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)